Multilevel perspectives on the antecedents of work design - Knight, Caroline; Van den Broeck, Anja; Tims, Maria; Gawke, Jason; Parker, Sharon; Scrimpshire, Alex; Wang, Cynthia; Edwards, Bryan; Ku, Gillian; Sarmah, Pallavi; Proost, Karin; Germeys, Filip; et al. (2020)
Despite the established relationships between good work design and outcomes, poor work designs continue to persist. Little research has yet investigated the causes of this phenomenon. In this symposium we investigate how multilevel distal antecedents of work design, such as organizational change, influence employee job crafting and managers’ job design behaviours, and also directly affect work design. The five included papers highlight novel antecedents of work design at different levels which are currently under-researched but which could have important implications for research and practice. We hope to stimulate conversation on the topic which helps to take this field forward in a timely manner. Despite the established relationships between good work design and outcomes, poor work designs continue to persist. Little research has yet investigated the causes of this phenomenon. A recent review – and to our knowledge the only review on this topic - highlighted that key antecedents of work design can be situated at multiple levels (Parker, Van den Broeck & Holman, 2017), including the global (e.g., international trade laws), national (e.g., employment regimes), occupational (e.g. values), organizational (e.g., HR practices, technology), group (e.g. team composition) and individual level (e.g., competence). These distal multilevel level factors then influence the proximal antecedents of work design in terms of employee job crafting and managers’ job design behaviours by impacting on their knowledge, skills, abilities, motivation and opportunities. Research on how employees change their job designs by crafting their work is expanding rapidly (Rudolph, Katz, Lavigne, & Zacher, 2017), and an initial experiment investigating the role of managers in the design of work indicated that people tend to design poor quality jobs unless they have experience as an organizational psychologist, work in high autonomous jobs, or are generally open to new experiences (Parker, Andrei & Van den Broeck, 2018). In this symposium, our goal is to take this work forward by further investigating how the multilevel distal antecedents of work design influence employee job crafting and managers’ job design behaviors and also directly affect work design. The included papers highlight novel antecedents of work design at different levels which are currently under-researched but which could have important implications for research and practice. We hope to stimulate conversation on the topic which helps to take this field forward in a timely manner.